How Does Social Media as Tools for Social Movements on Global Issues? A Systematic Literature Review - ., Wahyudi; ., Salahudin; Wahyudi, Fidela Dzatadini; Firdaus, Muhammad (Journal of Ecohumanism, 2024)
This study aimed to map the development of research and scientific publications about social movements on social media. This study used the Systematic Literature Review approach to analyze 471 scientific articles that were selected based on the PRISMA procedure. The articles were taken from the Scopus database published in the 2018-2023 period. Cite Space software was used to visualize the data such as topic clusters, authors, and topic trends in the study of social movements on social media. This study reveals that there are ten topic clusters in the study of social movements on social media, namely collective action (#0), long covid (#1), stock market (#2), umbrella movement (#3), social media (#4 ), environmentally-related migration (#5), racial justice (#6), extreme events (#7), influence odoj (#8), sexual abuse (9#), and systems research (10#). Collective action is the most dominant cluster compared to other clusters, which shows that collective action is a general concept used in the study of social movements on social media, which is related to various issues in other clusters, such as Covid-19, politics, racism, and the stock market. Each topic cluster was discussed by many authors with various study focuses, but all authors used the concept of social media as a social movement to explain the issues that were the focus of their respective studies. Trend topics in the study of social movements on social media show that social movements and social media are a unified concept that can be used to explain various issues to study. This research contributes to the development of social movement studies in the digital era, the internet, mobility networks, and artificial intelligence. The limitation of this research is that the data used were from the Scopus database only so the findings cannot fully explain the study of social movements on social media. Therefore, future research needs to use data or references from other reputable databases such as the Web of Science and EBSCO.